Autoantigens ADAMTSL5 and LL37 are significantly upregulated in active Psoriasis and localized with keratinocytes, dendritic cells and other leukocytes. Issue 11 (29th June 2017) - Fuentes‐Duculan, Judilyn; Bonifacio, Kathleen M.; Hawkes, Jason E.; Kunjravia, Norma; Cueto, Inna; Li, Xuan; Gonzalez, Juana; Garcet, Sandra; Krueger, James G.
Abstract: Psoriasis is a common immune‐mediated disease that affects 2%‐4% of individuals in North America and Europe. In the past decade, advances in research have led to an improved understanding of immune pathways involved in the pathogenesis of psoriasis and has spurred the development of targeted therapeutics. Recently, three psoriasis autoantigens have been described: cathelicidin (LL37), a disintegrin and metalloprotease domain containing thrombospondin type 1 motif‐like 5 (ADAMTSL5), and lipid antigens generated by phospholipase A2 (PLA2) group IVD (PLA2G4D). It is important to establish the expression, regulation and therapeutic modulation of these psoriasis autoantigens. In this study, we performed immunohistochemistry and two‐colour immunofluorescence on non‐lesional and lesional psoriasis skin to characterize ADAMTSL5 and LL37, and their co‐expression with T cells, dendritic cells, neutrophils and macrophages, which are the main immune cells that drive this disease. Our results showed that ADAMTSL5 and LL37 are significantly ( P <.05) increased in lesional skin and are co‐expressed by many dendritic cells, macrophages and some T cells in the dermis. Gene expression analysis showed significant ( P <.05) upregulation of LL37 in lesional skin and significant downregulation following treatment with etanercept. ADAMTSL5 and LL37 are also significantly decreased by IL‐17 or TNF‐α blockade, suggesting feed‐forward induction of psoriasis autoantigens by disease‐related cytokines.